The methodical deviations evaluation of two-port S-parameters measurement - Filyniuk, M. A.; Ohorodnyk, K. V. (Visnyk of Vinnytsia Politechnical Institute, 2010)
A new method of measurement of non-standard system of two-port S-parameters is offered. Experimental verification results of the suggested method are shown. The methodical deviations evaluation results of measurement of each S-parameters are discussed. The offered method has less number of operations in comparison with classic methods and it can be used over the whole microwave frequency range.